A new Philippine endemic species and new records of Lasianthus (Lasiantheae, Rubiaceae) - Arshed, Muhammad Jefte C.; Alejandro, Grecebio Jonathan D. (Phytotaxa, 2016)
A new species named as Lasianthus halconensis from Mt. Halcon, Mindoro, Philippines is described and illustrated. This species is easily distinguished from the other Lasianthus by having strigose indumentum on branches, abaxial leaf surface, petioles and calyx; lanceolate leaves, cuneate at base; obconical calyx and drupes with 8 pyrenes. This species is allied to L. obliquinervis and L. chrysoneurus but differs in stem, leaf and calyx indumentum, leaf and calyx shape and the absence of bracts. Moreover, three new records of Lasianthus in the country are reported including their diagnosis.